rozwiąż równania E)4x-7=33 f)-6x-3=-15 g)3(x-1) +2=-7 h)1-6/7 +x=4/7​

Odpowiedź :

[tex]e) \: 4x - 7 = 33 \\ 4x = 33 + 7 \\ 4x = 40 \: \: | \div 4 \\ x = 10[/tex]

[tex]f) \: - 6x - 3 = - 15 \\ - 6x = - 15 + 3 \\ - 6x = - 12 \: \: | \div ( - 6) \\ x = 2[/tex]

[tex]g) \: 3(x - 1) + 2 = - 7 \\ 3x - 3 + 2 = - 7 \\ 3x = - 7 + 3 - 2 \\ 3x = - 4 - 2 \\ 3x = - 6 \: \: | \div 3 \\ x = - 2[/tex]

[tex]h) \: 1 - \frac{6}{7} + x = \frac{4}{7} \: \: | \times 7 \\ 1 \times 7 - 7 \times \frac{6}{7} + x \times 7 = 7 \times \frac{4}{7} \\ 7 - 6 + 7x = 4 \\ 7x = 4 - 7 + 6 \\ 7x = - 3 + 6 \\ 7x = 3 \: \: | \div 7 \\ x = \frac{3}{7} [/tex]